2000
DOI: 10.1002/j.2048-7940.2000.tb01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the Relationship: The Experience of Primary Support Persons of Stroke Survivors

Abstract: The primary support persons (PSPs) of stroke survivors are faced with many challenges as they help reintegrate the stroke survivor's life, as well as their own. Because it often is the PSP with whom nurses negotiate goals, teach, and counsel, it is important for nurses to understand the stroke experience from the PSP's perspective. The purpose of this study was to investigate the quality, or nature, of life as experienced by PSPs of stroke survivors. The qualitative design for this study was an existential‐phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 16 publications
(21 reference statements)
2
36
1
Order By: Relevance
“…Whilst often it was implied that the interview was conducted by a member of the research team, the identity of the interviewer was rarely explicitly reported. The exceptions were five studies where a trained nurse [20], the primary investigator [21,27,29] or a research assistant [25] interviewed participants.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Whilst often it was implied that the interview was conducted by a member of the research team, the identity of the interviewer was rarely explicitly reported. The exceptions were five studies where a trained nurse [20], the primary investigator [21,27,29] or a research assistant [25] interviewed participants.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
“…Interviews were variously described simply as 'interviews', 'semi-structured', 'unstructured' and 'in-depth' interviews. One study [22] described their method as 'semi-structured, in-depth' interviewing and another 'phenomenological' interviewing [27]. Another used both interviews and observations [29] and another employed a semistructured survey and analysed participants' online discussions [26].…”
Section: Data Collection and Methodsmentioning
confidence: 99%
See 3 more Smart Citations